The Implementation of Government Regulation Number 23 of 2018 (PP 23) to The Tax of MSMEs - Sofie Yunida Putri; Acynthia Ayu Wilasittha (Nusantara Science and Technology Proceedings, 2021)
PP No. 23 of 2018 is one of the tax reforms carried out by the Government for MSME actors as a form of development of PP No. 46 of 2013. Through this research, it is hoped that it will be known how the effect of the application of PP No. 23 of 2018 on the amount of tax that must be paid by the perpetrators. SMEs. In addition, this study also aims to find out whether the implementation of PP No. 23 of 2018 can provide advantages or disadvantages for MSMEs. This type of research is a qualitative research with a comparative descriptive analysis approach where the researcher conducts comparisons and comparative analysis related to the simulation of tax calculations when MSMEs apply PP No. 23 of 2018.